Research progress on the role of neutrophil extracellular traps in treating chronic kidney disease fibrosis - Ying Chun-cheng; Zhang Shi-qiu; Luo Hui-dan; Zhu Yong-jun (Linchuang shenzangbing zazhi, 2025)
Neutrophil extracellular traps （NETs）， as the final stage of a novel and unique defense mechanism of neutrophils， play a critical role in the occurrence and progression of fibrosis in chronic kidney disease （CKD）. This article reviewed the various processes involved in NET formation and the mechanisms related to their roles in the activation of inflammatory responses， extracellular matrix （ECM） remodeling， and fibroblast activation. It also discussed the mechanisms of NETs in the occurrence and development of different types of CKD， with the aim of providing new insights into the elucidation of mechanisms of CKD-associated fibrosis and offering potential therapeutic targets.